Confirmatory factor analysis ols unweighted a scale of attitudes toward the duel - Chávez Carapia , Julia del Carmen (Consorcio de Universidades Mexicanas A.C., 2016)
Die theory states that the demographic trend of births, marriages, divorces, deaths and life expectancy evidence a scenario of permanent mourning in population dynamics. In the states with a majority of young people and therefore an accelerated rate of reproduction and birth as the State of Mexico, there is a greater probability of mourning when considering the lifestyles and risk behaviors. The aim of this work is confirmed by least squares the factorial structure of the scale of attitudes towards the Duel (EAD) Garcia (2010) and discuss both its scope and limits facing Scale Fear of Death (FDS), the multiscale Fear of Death (MFDS), Depression Scale to Death (DDS) and Life Purpose Scale (PLS). a non-experimental and cross-sectional study with a nonrandom selection of 260 students of a public university was held. Research on the structure of ODL multitrait will explore are noticed.